Pengetahuan Tentang HIV/AIDS Berhubungan Dengan Konseling HIV/AIDS pada Ibu Rumah Tangga HIV/AIDS - Sundari Mulyaningsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
The number of HIV/AIDS in Indonesia is more increasing and its distribution has been very complex. Now, HIV/AIDS is also attacking housewives, whose activity is mostly at home. In Yogyakarta, there are many obstacles to the practice of taking ARV, because of the less openness of HIV/AIDS sufferers, uncontrollable distribution and irregular consumption of ARV. The purpose of this research is to know investigate the relation between the knowledge of HIV/AIDS and the counseling of HIV/AIDS among housewives with HIV/AIDS in Yogyakarta. This research is quantitative study with a cross-sectional approach. The sample is 47 housewives with HIV/AIDS. The data was collected through the interview using a structured questionnaire and analyzed by chi-square to know investigate the relation between the knowledge of HIV/AIDS and the counseling of HIV/AIDS. This research showed that the majority of respondents had less knowledge about HIV/AIDS (61.7%) and did not attend counseling (59.6%). The analysis between two variables using chi-square result p=0.000, it means that there was a correlation between knowledge of HIV/AIDS and the counseling of HIV/AIDS among housewives with HIV/AIDS in Yogyakarta.